1986
DOI: 10.1523/jneurosci.06-07-02012.1986
|View full text |Cite
|
Sign up to set email alerts
|

Effects of nerve growth factor on the survival and synaptic function of Ia sensory neurons axotomized in neonatal rats

Abstract: Sensory neurons with small diameters (A delta and C cells) are known to be responsive to exogenous NGF even at postnatal stages. We have examined whether large Group Ia sensory neurons (A alpha cells) arising from muscle spindles are also responsive to NGF in neonatal rats. For this purpose, monosynaptic excitatory postsynaptic potentials (EPSPs) were evoked in spinal motoneurons by Group Ia muscle afferent volleys. When a muscle nerve was crushed on the day after birth, the monosynaptic EPSPs elicited by affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
61
0
3

Year Published

1986
1986
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 120 publications
(72 citation statements)
references
References 29 publications
8
61
0
3
Order By: Relevance
“…and Methods Surgical procedures were exactly the same as those described in the previous paper (Miyata et al, 1986). Wistar rats were anesthetized with ether the day after birth, and the nerve to the medial gastrocnemius (MG) muscle was crushed with a Dumont forceps at the bifurcation point near its entry to the muscle in the left hind leg.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…and Methods Surgical procedures were exactly the same as those described in the previous paper (Miyata et al, 1986). Wistar rats were anesthetized with ether the day after birth, and the nerve to the medial gastrocnemius (MG) muscle was crushed with a Dumont forceps at the bifurcation point near its entry to the muscle in the left hind leg.…”
Section: Methodsmentioning
confidence: 99%
“…The preceding study (Miyata et al, 1986; also see Kuno et al, 1985) showed that monosynaptic excitatory postsynaptic potentials (EPSPs) evoked in spinal motoneurons by muscle afferent volleys are strikingly depressed following crush of the muscle nerve in neonatal rats and that this synaptic depression is partially reversed by daily treatment with NGF. Thus, the central synaptic function of Group Ia sensory fibers in neonatal animals appears to be influenced by exogenous NGF under certain conditions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly. Miyata et al (1986) had reported a significant increase in the loss of motoneuron cell bodies after crush lesion of the medial gastrocnemius nerve of newborn rats after treatment with NGF (289c death after lesion in the absence of NGF, increased to 429c in NGF treated animals). At the concentration of NGF with which we obserye a reduction in BDNF-mediated motoneuron survival in vitro.…”
Section: Effects Of Combinations Of Survival Factors Formentioning
confidence: 99%
“…Spinal neural circuits undergo continuous functional and structural changes in response to a peripheral nerve injury (2). Some recent studies show that glutamate receptors may be involved in sensory and motor neuron apoptosis following severe nerve injury in rats (14,17,25,50). Glutamate is an important excitatory neurotransmitter in the nervous system.…”
mentioning
confidence: 99%